Effects of emicizumab on APTT, one‐stage and chromogenic assays of factor VIII in artificially spiked plasma and in samples from haemophilia A patients with inhibitors. Issue 3 (6th April 2020) - Bowyer, Annette; Kitchen, Steve; Maclean, Rhona
Abstract: Introduction: Emicizumab (Hemlibra, Roche‐Chugai) is a recombinant humanized bispecific IgG4 antibody which mimics some of the actions of activated factor VIII (FVIIIa) by binding to factor X (FX) and activated factor IX (FIXa) to activate FX. Aim: To evaluate the effect of emicizumab on the APTT, standard one‐stage APTT‐based FVIII activity assay (sOSA) using plasma calibrators, modified OSA (mOSA) using r 2 Diagnostics emicizumab specific calibrator and chromogenic FVIII assays. Tests were performed on plasma artificially spiked with emicizumab and from four severe haemophilia A (SHA) patients treated with emicizumab. Method: APTT in spiked plasma was performed with 13 APTT reagents and in SHA patients with 5 reagents. OSA in spiked plasma was performed with 9 APTT reagents, 7 APTT reagents were used for OSA in SHA patients and six chromogenic substrate assays (CSA) were performed. Results: In SHA, APTTs normalized after the first dose of emicizumab. At weeks 32/36 of treatment, the mean sOSA FVIII:C ranged from 2.47 IU/mL (Synthasil) to greater than 7.00 IU/mL with all other reagents. mOSA ranged from 59.8 µg/mL (Synthasil) to 74.5 µg/mL (APTT SP). Bovine CSA did not recover any FVIII:C activity. Hyphen Biomed human CSA, demonstrated FVIII activity when calibrated against a plasma calibrator. Conclusion: The APTT was significantly shortened in the presence of emicizumab. sOSA FVIII:C levels were erroneously high, and it is not recommended that these be performed. Quantification of emicizumab concentration was possible by mOSA. Human CSA was sensitive to emicizumab and surrogate FVIII:C activity could be determined. Bovine CSA were insensitive to emicizumab and could not be used to quantify emicizumab concentration.